Pengaruh Motivasi dan Independensi Auditor Terhadap Kinerja Auditor - Mariana, Mariana; Rahmaniar, Rahmaniar (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2022)
The purpose of this study was to determine the effect of motivation and auditor independence on auditor performance at the inspectorate in the Aceh region. The data analysis method in this study uses multiple linear regression to predict the effect of the independent variables. The data analysis method in this study uses multiple linear regression to predict the effect of the independent variables. The population in this study were all auditors, namely 23 District/City Inspectorates in Aceh Province, from which 64 samples were obtained. The results of the study indicate that motivation affects auditor performance, this shows that there is encouragement from individual auditors that can increase the level of aspiration of quality audit urgency, toughness, tenacity, and consistency. Auditor independence affects the performance of the auditor, this shows that the auditor has an independent attitude that can improve performance. Independently hired auditors to act.